Gut Microbiota Alterations from Three-Strain Yogurt Formulation Treatments in Slow-Transit Constipation. (19th February 2020) - Li, Xiao-Ran; Liu, Chen-Jian; Tang, Xiao-Dan; Zhang, He-Ming; Luo, Yi-Yong; Zhang, Le; yang, En
Abstract : The objective of this study was to evaluate the effects of a three-strain yogurt formulation in slow-transit constipation (STC) patients. Each individual in both treatment groups consumed 250 mL of the formulated yogurt daily for a week (7 days), and fecal samples were collected for gut microbiota and short-chain fatty acid (SCFA) analyses. A significant increase in the defection frequency (p < 0.001 ) and bacterial diversity (p = 0.027 ) at the 100% sequence homology level and a decrease in the concentrations of acetic acid (p = 0.014 ), propionic acid (p = 0.019 ), and butanoic acid (p = 0.005 ) were observed after the STC patients consumed three-strain yogurt formulation. In addition, the consumption of the three-strain yogurt formulation significantly altered the composition of the intestinal bacteria in the STC patients. The relative abundances of 23 genera in the top dominating genera were altered significantly after the STC patients consumed the yogurt. In summary, the consumption of 250 mL day − the three-strain yogurt formulation described in this study can play a role in improving the symptoms of STC.